Need Analysis of Translation Contents And Islamic Contents For English Translation Subject - Warna, Dewi; Mardiah, Anisatul; Nurlatiffah, Nurlatiffah (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2023)
Need analysis is the first step in building a course or creating learning materials. It collects information from the research participants regarding their educational needs. This study investigated the students' need for Translation and Islamic contents in Translation class. The method of research was descriptive and quantitative The study participants were 105 sixth-semester students from four classes at the English Education Study Program of the Faculty of Tarbiyah and Teaching Sciences, UIN Raden Fatah Palembang, who had passed the Translation Subject. A survey technique was used to collect the data. The researcher also interviewed eight students to uncover why they tended to choose some more needed content than the other contents in terms of translation and Islamic contents. The quantitative data obtained through questionnaires was analyzed using the Likert scale. Then, the result was put in the form of a percentage, which was arranged from very needed to not needed at all. The findings showed that first, for translation contents, in terms of the topics of texts to be translated in Translation Subject that are highly needed, are the ones in the field of language skills (55.2%); second, in terms of the language texts to be translated that are highly needed, are the ones written in English (41.9%); third, in terms of the level of texts to be translated that are highly needed, are the ones with high level (41.9%); and fourth, in terms of the genre of texts to be translated that are highly needed, are the ones with the genre of job application letter (42.9%); While, for Islamic contents, first, in terms of aqidah contents of texts to be translated in Translation Subject that are highly needed, are the ones consisting of rukun Islam (32.4%); second, in terms of akhlak contents of texts to be translated that are highly needed, are the ones comprised of the influence of socialization in life (35.2%); third, in terms of Al-Qur’an contents of texts to be translated that are highly needed, are the ones consisting of the privileges of the Qur’an (49.5%); and fourth, in terms of fiqih and muammalah contents of texts to be translated that are highly needed, are the ones consisting of rukun of prayer (27.6%).